Reformasi Pendidikan: Integrasi Nilai-Nilai Tradisionalisme dan Modernisme dalam Pendidikan Islam - Muhammad Arroyan (Universitas Muhammadiyah Prof Dr Hamka, 2024)
This study aims to find common ground on Islamic education reform that combines traditionalism (religious knowledge, morals, exemplary teachers) and modernism (technology, critical thinking, 21st century skills) through a balanced curriculum, varied methods, conducive environment to produce superior generations who are able to answer challenges. This research was conducted by analysing literature related to traditionalism, modernism and Islamic education. Data were collected from relevant articles, books and scientific journals. Descriptive-qualitative analysis was conducted to find the principles of modernism and traditionalism that can be incorporated into Islamic education. The results show that the principles of traditionalism, such as understanding of religious sciences, morality, and teacher personality, can be integrated with the principles of modernism, such as technological capabilities, critical thinking, and modern skills. With a balanced curriculum, varied learning approaches and a conducive learning environment, this integration can be achieved. The study concludes that by combining the values of modernism and traditionalism, Islamic education reform can produce human beings who have a balance between religious and general knowledge and are able to compete in the modern era. This is important to answer the challenges of the times and produce a generation that excels intellectually, religiously and socially.